Tradition in the Work of Eugene Delacroix. Romantic Painting of the 1820s and the Art of the Old Masters - Goikhman, Elena G. (Actual Problems of Theory and History of Art, 2025)
The essential characteristic of the French romantic painting of the 1820s is the combination of the old styles (Venetian art, Spanish school, Baroque style) and new subjects (literature, historical anecdotes, life of exotic oriental civilizations). The greatest pictures of E. Delacroix are inspired by the representations of heavenly appearances, triumphs and apotheoses widespread in the art of the 17th c. Delacroix keeps the traditional compositional scheme, yet he changes the roles and emotional connections between his personages. All these means are intended by Delacroix to affect the imagination of his spectators.